MEMBEDAH PENAFSIRAN CORAK ILMI DALAM AL-QUR’AN DAN TAFSIRNYA (EDISI YANG DISEMPURNAKAN) TAHUN 2011 KARYA KEMENTERIAN AGAMA RI - Nurfadillah, Shinta; Saputra, Ali Thaufan Dwi (Ushuluna: Jurnal Ilmu Ushuluddin, 2023)
The author’s main concern in this study is to try to “dissect interpretations” with a scientific approach in Al-Qur’an dan Tafsirnya (Edisi Yang Disempurnakan Tahun 2011) compiled by a team appointed by the Ministry of Religion of the Republic of Indonesia. To dissect these scientific approach, the author uses the conceptions of interpretation scholars regarding the interpretation of scientific approach. The interpretation of the scientific approach is a focuses on discussing the verses of the al-Qur’an which contain scientific cues so that the meaning and purpose expressed in them can be understood in detail. This study uses a data source in the form of library data. The type of research viewed from the perspective of implementation in this research is descriptive research. Researchers attempt to describe the object of study studied in depth. The main question to be answered in this study is: how many verses are interpreted in a scientific approach in the Al-Qur’an dan Tafsirnya (Edisi Yang Disempurnakan Tahun 2011) from juz 6 to juz 10?, and what is the background for the drafting team to pay more attention to interpretation scientific in it? The findings of this study indicate that in juz 6 to 10, there are 9 verses that are interpreted using a scientific approach. Interpretation with a scientific approach was carried out by a drafting team appointed by the Ministry of Religion of the Republic of Indonesia because they considered that society needed a new perspective in interpretation, a scientific approach. It is also based on the rapid development of science.